High potential of affordable housing supply by using industrialised building system in Selangor - Mohamed Aris, N A; Fathi, M S; Harun, A N; Mohamed, Z (IOP conference series. Earth and environmental science, 2020)
The implementation of an industrialized building system (IBS) by housing developers has been a subject of argument in terms of reducing the overall costs of the housing projects which aim to sustain the supply of affordable houses to the people. To date, no real-world study has been conducted into real business cases. Thus, this case study has been carried out to verify the utilization of IBS in reducing the construction cost of housing projects. Three case studies based on interviews were reviewed and analyzed using the content analysis approach. The findings showed that there were significant differences between utilizing the IBS approach compared to the conventional method. However, the factors of volumes, IBS supplier radius, land acquisition, design, type of residential units and construction company capacity are the main concerns which have been emphasized in applying the IBS method for affordable housing supply by the developers and manufacturers. The most interesting outcome was the fast completion of the construction projects which resulted in speeding up the claiming process. Thus, the implementation of IBS will enhance the developers' cash flow. This study concludes that the high potential of utilizing IBS components in affordable housing programs can be related to the overall reduction of construction costs, since more units were planned to be constructed in Selangor. However, the affordable housing program agencies should play a vital role in land acquisition.